Geo-Informatics for the Future: A Systematic Literature Review on the Role of WebGIS in Infrastructure Planning and Development - Kurniawan, Dedy; Indah, Dwi Rosa; Sari, Purwita; Akbari, Rahmat Alif (AI Society & STMIK Indonesia, 2023)
The crucial role of geographic information in contemporary transportation infrastructure planning underscores the need for efficient and practical tools. This systematic literature review aims to provide a comprehensive overview of the current evidence concerning Web Geographic Information Systems (WebGIS) application in infrastructure planning. It further identifies potential avenues for future research. The study leverages digital libraries to source peer-reviewed papers and published journals, evaluating the characteristics and applications of WebGIS. The review offers an in-depth analysis of WebGIS implementation, focusing on flexibility, location, utilized sectors, and environmental impacts. The methodology involves identifying research topics, developing a search plan, and selecting relevant articles using rigorous search techniques. The selected articles undergo a thorough quality assessment before data extraction. This review seeks to answer key research questions: How does WebGIS aid infrastructure management in agricultural settings? Can WebGIS be implemented free of charge? Is it flexible and user-friendly? Can WebGIS address the issue of declining seawater quality? Has WebGIS been successfully implemented for infrastructure planning globally? This review aims to shed light on the potential of WebGIS in shaping future infrastructure planning and to encourage further exploration in this field.